Unmet Need for Modern Contraceptive Methods Among Displaced Married Women in Their Reproductive Years in Bishan Guracha Town, West Arsi Zone, Oromia Region, Ethiopia - Sisay Million; Zeleke Gebru; Sultan Hassen; Selamnesh Tesfaye (Hindawi Limited, 2024)
Conclusion and Recommendations: The magnitude of the unmet need for modern contraceptive methods was higher than both the Ethiopian national and Oromia regional state total unmet need for the general population. Governmental and nongovernmental organizations should increase their efforts to reduce this high magnitude of unmet needs by emphasizing those factors that have a great contribution to unmet needs.